(untitled) (Revista Internacional de Folkcomunicação, 2018)
The celebrations of the feast of the Magi in Spain, recorded by diverse habits and manifestations of a religious and cultural syncretism, translate one of the approaches of the Folkcommunication, according to Luiz Beltrão’s conceptual characterization (1980 and 2001). In addition to a national holiday, the January 6 ’Iberian’ is marked by parades (cavalcade) of cars decorated by an annual theme, delivery of gifts for children, eating habits (such as the "roscón de reyes") and even a gambling (lottery of the child), among other actions and media strategies that characterize the festivals of kings in Spain. This study, based on field research of ethnographic character and clippings of media productions that thematicised the party, is an event that can be characterized as a contemporary folk-communicational expression. Folkcomunicação; Festividy of kings; cultural syncretism; cavalcade of kings in Spain; Cultural journalism.